2022
DOI: 10.1007/s11242-022-01774-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Immiscible Fingering on the Mechanism of Secondary and Tertiary Polymer Flooding of Viscous Oil

Abstract: Immiscible viscous fingering in porous media occurs when a low viscosity fluid displaces a significantly more viscous, immiscible resident fluid; for example, the displacement of a higher viscosity oil with water (where μo >  > μw). Classically, this is a significant issue during oil recovery processes, where water is injected into the reservoir to provide pressure support and to drive the oil production. In moderate/heavy oil, this leads to the formation of strong water fingers, bypassed oil and high/ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Given the low frontal advance rate in these experiments ~0.005 m/day, it is expected that there will not be sufficient variance in shear rate to significantly impact the in situ viscosity. A low sensitivity to injected viscosity was noted by Beteta et al (2022) [ 31 ] in similar permeability Bentheimer cores during displacement of oil and direct simulation matches of the experiments were obtained using the methodology from Sorbie et al (2020) [ 16 ] assuming a Newtonian fluid.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…Given the low frontal advance rate in these experiments ~0.005 m/day, it is expected that there will not be sufficient variance in shear rate to significantly impact the in situ viscosity. A low sensitivity to injected viscosity was noted by Beteta et al (2022) [ 31 ] in similar permeability Bentheimer cores during displacement of oil and direct simulation matches of the experiments were obtained using the methodology from Sorbie et al (2020) [ 16 ] assuming a Newtonian fluid.…”
Section: Methodsmentioning
confidence: 80%
“…Permeability distribution ranges from 0.01 to 10 D with an average of ~3 D. The effect of this permeability range of (k max /k min ) is examined below. Sensitivities to grid resolution and correlation length have been previously presented, and as such are not repeated here [ 15 , 16 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Following this work the methodology has been shown to be capable of directly matching both core and slab scale experiments across a wide range of oil viscosities (µ o /µ w 100-7,000) (Beteta et al, 2022a, b). Furthermore, (Beteta et al, 2022a) showed the methodology could predict the impact of reducing the injection uid viscosity and veri ed this with further core ooding experiments.…”
Section: Introductionmentioning
confidence: 77%
“…The rst step in the numerical modelling of viscous ngering systems, determining factional ow and generation of relative permeability curves from laboratory data, has been presented in a previous publication (Beteta et al, 2022a). This work utilised the methodology proposed by Sorbie et al (2020) for simulating two phase immiscible viscous ngering.…”
Section: Simulation Backgroundmentioning
confidence: 99%
See 1 more Smart Citation